Digital Assessment: Empowering 21st Century Teachers in Analyzing Student’s Performance in Calamba City - Palanas, Dexter; Alinsod, Anthony; Capunitan, Paulo (JPAIR Institutional Research, 2019)
Educators utilize students’ scores on standardized tests to evaluate the impact of instructional programs designed to improve student achievement. Thus, a data-driven-decision is crucial in policy formulation and the development of the interventions in addressing the gaps in education. The rationale of this study is to ensure the accuracy and validity of consolidated assessment data and to provide appropriate responses using checking and analysis software applications. The study used a descriptive quantitative design. A questionnaire was given to the participants relative to their perception and reflection on the use of software application in assessment for the school year 2018 – 2019. The research was limited to the effectiveness of the software application in terms of checking, scoring, recording, organizing, analyzing, and reporting assessment data. The results show that assessment software application has a significant difference compared to traditional assessment procedures in terms of a) provision of accurate and valid data, b) cost-effectiveness, c) flexible features in organizing and analyzing data, and d) speed of providing feedback. The study implied the importance of how teachers should adapt to emerging technology, specifically, on software that may help them not only in assessment but also in instruction. As a recommendation, the formulation of local policy on digital evaluation should be implemented.
Keywords: Education; assessment; software application; descriptive quantitative design; Philippines